2000
DOI: 10.1007/s00585-000-1172-x
|View full text |Cite
|
Sign up to set email alerts
|

Auroral <i>E</i>-region electron density gradients measured

Abstract: Abstract. In the theory of E-region plasma instabilities, the ambient electric ®eld and electron density gradient are both included in the same dispersion relation as the key parameters that provide the energy for the generation and growth of electrostatic plasma waves. While there exist numerous measurements of ionospheric electric ®elds, there are very few measurements and limited knowledge about the ambient electron density gradients, rN e , in the E-region plasma. In this work, we took advantage of the EIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Unsurprisingly, Haldoupis et al. (2000) found that L z takes on larger values at higher altitudes in the topside ionosphere, that is, from 10 km to greater than 25 km.…”
Section: Theory Of E‐region Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, Haldoupis et al. (2000) found that L z takes on larger values at higher altitudes in the topside ionosphere, that is, from 10 km to greater than 25 km.…”
Section: Theory Of E‐region Instabilitiesmentioning
confidence: 99%
“…At high latitudes, the magnetic field is near‐vertical. In order to get the appropriate value of L x , the magnetic dip angle ( I ) must be taken into account (Haldoupis et al., 2000): Lx=Lzcos(I) ${L}_{x}=\frac{{L}_{z}}{\cos (I)}$ …”
Section: Theory Of E‐region Instabilitiesmentioning
confidence: 99%
“…Haldoupis et al (2005) in di cated that the past ob ser va tions of HF and VHF au rora ra dar (e.g., Hanuise el al. 1991;Haldoupis et al 2000;Lacroix and Moorcroft 2001) could not find GD ef fect on FB waves, but ne glected a point that the very strong po lar ized elec tric field might ex ist in au rora re gion. The past stud ies of ra dar ob ser va tions (e.g., St.-Maurice et al 1986;Ravindran and Reddy 1993;Nielsen et al 2002) also in di cated that the large elec tron drift ve loc ity de rived from strong elec tric field would heat plasma and cre ate larger phase ve loc ity.…”
Section: Sum Mary and Discussionmentioning
confidence: 95%
“…It was also ap plied ex ten sively in nu mer ous stud ies such as the in ter preta tions of types 3 and 4 VHF au rora ech oes (e.g., see a review by Moorcroft 2002). In situ rocket mea sure ments (Haldoupis et al 2000(Haldoupis et al , 2005 of E-re gion elec tron den sity pro file had shown that the den sity gra di ents ex isted widely in any lat i tude E-re gion of 100 -110 km al ti tude, and that the scale lengths of the destabilized plasma den sity gra di ent orig i nated from spo radic E layer were smaller than 2 km. How ever, Haldoupis et al (2005) ar gued against a den sity gra di ent ef fect on short-scale FB waves, be cause they found no gra di ent drift ef fects on low er ing the FB in sta bil ity thresh old and the wave length de pend ence of phase ve loc ity by the ob ser va tion of two ra dar fre quen cies at 144 and 50 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Incoherent scatter radar measurements [Haldoupis et al, 2000;Yin et al, 2008;Mitchell et al, 1998] have previously shown that during strong precipitation events, enhancements in E region electron density can reach up to 4 Â 10 11 electrons per cubic meter over an extended altitude range. Projecting this electron density over, for example, an arbitrary 50 km vertical distance equates to $2.5 TECU.…”
Section: Particle Precipitationmentioning
confidence: 99%